P233 Do you see what I see? Teaching Gastroenterology trainees how to report endoscopic findings. (25th January 2019) - Hart, L; Chavannes, M; Lakatos, P L; Afif, W; Bitton, A; Bressler, B; Bessissow, T
Abstract: Background: The skills in endoscopy go beyond technical competence. Trainees should be able to accurately describing findings, as this can significantly affect management. We aimed to determine whether a web-based (WB) module can teach trainees how to accurately describe lesions in inflammatory bowel disease (IBD). Methods: In this pilot study, we designed an interactive WB module that provided education on IBD lesions. First, trainees were taught the descriptors used to explain the presence of inflammation. Thereafter, they were taught how to use the Mayo Endoscopic score (MES) for ulcerative colitis and the simple endoscopic score for Crohn's disease (SES-CD). They completed a 6 question image-based pre-test (asking them to describe a lesion, score it using the MES or SES-CD, and rate its severity as healed, mild, moderate, or severe). After completing the module, they completed a different six question image-based post-test and a satisfaction questionnaire. Both pre-test and post-test included images with varying severity of disease (that had been previously validated by three IBD experts). We assessed inter-rater agreement among the trainees, as well as improvement in test scores before and after the intervention (for describing lesions and disease severity). The IBD expert answers were used as the correct answers (for comparison purpose). Furthermore, we compared post-test results to a historic cohort of trainees who had not received the module. Results: In total, 23 trainees completed the pre-test, compared with 30 trainees who completed the post-test and 32 trainees in the historic cohort. The pre-module and post-module total test score were unchanged at 7/12 (58.3%, pre-module IQR 5.5–8, post-module IQR 5–8, p = 0.83). Similarly, there was no difference between the pre-module and post-module subscore for MES (66.7% IQR 33.3–66.7%, p = 0.89). While not reaching significance ( p = 0.07), there was an increase in the subscore for SES-CD from pre to post-module (33.3 IQR 33.3–66.7 to 66.7% IQR 33.3–66.7%), with the post-module subscore also correlating with the historic cohort. The accuracy in lesion description improved significantly from pre-module (54.5%, IQR 45.5–63.6%) to post-module (68.8% IQR 62.5–75%) assessments ( p < 0.001). For lesion description, the post module score was again comparable to the historic cohort (68.8% IQR 50.0–75.0, p = 0.78). Conclusions: In this pilot study, our WB interactive module led to improvement of trainees' ability to describe IBD lesions on colonoscopy. However, it did not lead to improvement in the use of IBD scoring systems. Further research with a larger cohort is needed to determine why there was a gap in knowledge and how to modify this teaching tool accordingly.